Search for axion-like particles through nuclear Primakoff production using the GlueX detector; Physics Letters B; Vol. 855 - Pybus J. R.; Kolar T.; Devkota B.; Sharp P.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2024, 2024)
Title screen